2015
DOI: 10.4103/0974-8490.157957
|View full text |Cite
|
Sign up to set email alerts
|

Review of clinical studies of Polygonum multiflorum Thunb. and its isolated bioactive compounds

Abstract: Polygonum multiflorum Thunb. (PMT), officially listed in the Chinese Pharmacopoeia, is one of the most popular perennial Chinese traditional medicines known as He shou wu in China and East Asia, and as Fo-ti in North America. Mounting pharmacological studies have stressed out its key benefice for the treatment of various diseases and medical conditions such as liver injury, cancer, diabetes, alopecia, atherosclerosis, and neurodegenerative diseases as well. International databases such as PubMed/Medline, Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 113 publications
0
28
0
1
Order By: Relevance
“…Radix Polygoni Multiflori (RPM, Heshouwu in Chinese), the tuberous roots of Polygonum multiflorum unb. (Polygonaceae), is one of the most popular traditional Chinese medicines (TCMs) and has been used to treat hyperlipidemia, coronary heart disease, neurosis, and other diseases commonly associated with aging in China and other Asian countries for many centuries [1][2][3]. Besides its medical uses, RPM has been made as tonic food and beverages and has become popular as a result of the growing interests of general population in phytonutrients and alternative medicines during the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Radix Polygoni Multiflori (RPM, Heshouwu in Chinese), the tuberous roots of Polygonum multiflorum unb. (Polygonaceae), is one of the most popular traditional Chinese medicines (TCMs) and has been used to treat hyperlipidemia, coronary heart disease, neurosis, and other diseases commonly associated with aging in China and other Asian countries for many centuries [1][2][3]. Besides its medical uses, RPM has been made as tonic food and beverages and has become popular as a result of the growing interests of general population in phytonutrients and alternative medicines during the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…There are two forms of PM decoctions in the Chinese Pharmacopoeia (2015): Raw Radix P. multiflorum (RPM) and P. multiflorum Preparata (PMP). While RPM contributes to detoxification and bowel relaxation, PMP tonifies the liver and kidney, benefits essence of blood and black beard, and relieves hyperlipidemia, fatty liver, and osteoporosis (Xuan et al, 2007;Wang et al, 2014;Bounda and Feng, 2015). Several clinical studies have been conducted to evaluate the traditional therapeutic claims including antiinflammatory bioactivity, dyslipidemia, sleep disorders, neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
“…P. multiflorum praeparata (PMP) is used more frequently in clinical practice mainly because of its tonic and anti-aging effects, whereas PM is commonly applied to resolve toxins, moisten the intestines and free stools (China Pharmacopoeia Committee, 2015 ). Modern pharmacological studies and clinical practice have indicated these two medicines have various biological activities, including anti-tumor, anti-oxidative, anti-bacterial, anti-hyperlipidemia, anti-atherosclerosis, immunomodulating and hepatoprotective effects (Bounda and Feng, 2015 ; Lin et al, 2015a ; Li et al, 2016a ). The chemical profiles demonstrate that stilbenes and anthraquinones are the major characteristic constituents, of which 2,3,5,4′-tetrahydroxystilbene-2- O -β-glucoside (TSG), emodin-8- O -β-D-glucoside (EMG), and physcion-8- O -β-D-glucoside (PG) are found to be dominant in PM, while PMP mainly contains TSG, emodin and physcion (Bounda and Feng, 2015 ; Lin et al, 2015a ; Li et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%